Cognitive Bias and the Extraversion Personality Shaping the Behavior of Investors - Ishfaq, Muhammad; Nazir, Mian Sajid; Qamar, Muhammad Ali Jibran; Usman, Muhammad (Frontiers in Psychology, 2020)
The paper examines the direct and indirect effects (via investors’ risk perception) of heuristic biases on investors’ irrational behavior in decision-making. The study also investigates the moderating effect of investors’ extraversion on both the direct and the indirect associations between heuristic biases and irrational decision-making. Based on survey data collected from 247 investors registered in various brokerage houses in Pakistan and the analyses (mediation and moderation) performed using the Process Macro technique (proposed by Hayes, 2017) in SPSS, the results of this study reveal that heuristic biases positively affect investors’ irrational decision-making both directly and indirectly via risk perception. The results reveal that extraversion moderates both direct and indirect associations between heuristic biases and investors’ irrational behavior in decision-making. Our findings carry useful practical implications for organizations’ policymakers.